Process modification of a wire-welding plant for efficient sulphate removal - (:unkn) unknown (WILEY, 2012)
Sulphate removal by chemical precipitation from the wastewater of a wire-welding facility was investigated. Sulphate was precipitated by using limestone and a small amount of lime. Firstly, the relationship between the ionic strength of wastewater and sulphate removal efficiency was established. A kinetic study of sulphate precipitation was also conducted. Finally, modification of plating process was proposed to achieve the highest sulphate removal. According to the suggested modification, the sulphate concentration of final discharge could be down to 425 mg/L. Hence, if wire-welding facilities modify their systems so that the wastewater is treated at the highest level of sulphate contents, the removal efficiency will be the highest, i.e. lesser amounts of sulphate will be discharged into sewage systems.
Keywords: calcium sulphate; lime; limestone; process modification; solubility; sulphate removal; wire welding; HEAVY-METAL IONS; CALCIUM-SULFATE; PRECIPITATION; DIHYDRATE; SOLUBILITY; ACID; WATER